PLATELET INDEXES FOR BACTERIAL SEPSIS SEVERITY ASSESSMENT - Michelle Hendriani Djuang; Fransiscus Ginting; Herman Hariman (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2018)
Sepsis is an infection-induced syndrome, mostly caused by bacteria, of organ dysfunctions caused by host response dysregulations. One of the simplest sepsis-indicator is platelet. This study aimed to determine whether platelet indexes i.e. Immature Platelet Fraction (IPF), platelet count, Mean Platelet Volume (MPV), plateletcrit (Pct), and Platelet Distribution Width (PDW), could assess sepsis severity by procalcitonin (PCT). This cross-sectional study was conducted at the Department of Clinical Pathology Adam Malik Hospital Medan from October to December 2016. Patients who had their full blood count examined with increased PCT ≥0.05 ng/mL were included. Sixty four of 71 patients with increased PCT were included in this study and separated into 3 groups based on their PCT levels (I = ≥0.05 – <2 ng/mL; II = ≥2 - <10 ng/mL; III = ≥10 ng/mL). Platelet count and plateletcrit showed a significant decrease when group I or II were compared to group III (p <0.05), but when the group I was compared to the group II there was no significance. On the other hand, the other platelet indexes showed no significance amongst the groups. Higher sepsis severity based on PCT affected more of the platelet number, as the result of platelet destructions caused by pro-inflammatory cytokines and endotoxins.